2021
DOI: 10.1111/eci.13501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real‐time and droplet digital PCR to detect and quantify SARS‐CoV‐2 RNA in plasma

Abstract: Background:The presence of SARS-CoV-2 RNA in plasma has been linked to disease severity and mortality. We compared RT-qPCR to droplet digital PCR (ddPCR) to detect SARS-CoV-2 RNA in plasma from COVID-19 patients (mild, moderate, and critical disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Our finding that measurement using qPCR and ddPCR are highly correlated is consistent with other studies in nasopharyngeal swabs (Falzone et al 2020, Liu et al 2020), plasma (Tedim et al 2021), wastewater from aircraft and cruise ships (Ahmed et al 2020), and raw influent (Cieselski et al 2021). However, we observed that the correlation became weaker at the lower end of the concentration range we tested, spreading out at lower concentrations in a “broom-shaped” pattern consistent with studies comparing measurements of bacterial targets (Cao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that measurement using qPCR and ddPCR are highly correlated is consistent with other studies in nasopharyngeal swabs (Falzone et al 2020, Liu et al 2020), plasma (Tedim et al 2021), wastewater from aircraft and cruise ships (Ahmed et al 2020), and raw influent (Cieselski et al 2021). However, we observed that the correlation became weaker at the lower end of the concentration range we tested, spreading out at lower concentrations in a “broom-shaped” pattern consistent with studies comparing measurements of bacterial targets (Cao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, digital PCR (dPCR) has emerged as an attractive alternative for environmental applications as it offers absolute quantification without the need for a standard curve, and it may be more sensitive and less prone to inhibition (Cao et al, 2015). As applied to the detection of SARS-CoV-2, RT-dPCR has been reported to be superior to RT-qPCR for clinical specimens, including nasopharyngeal samples (Falzone et al, 2020;Liu et al, 2020;Suo et al, 2020) and plasma from infected patients (Tedim et al, 2021), as it was found to be more sensitive and accurate.…”
Section: Pcr Platformsmentioning
confidence: 99%
“…An overall of 3651 samples, from 2825 patients and 145 controls, were extracted from the 39 included studies. The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although most eligible studies of this systematic review evaluated the diagnostic performance of ddPCR compared to RT-qPCR, we also extracted data from 10 studies assessing the prognostic performance of ddPCR and their main findings are summarized in Table 2 . Four of them showed that ddPCR can accurately quantify SARS-CoV-2 RNA levels, especially in immunocompromised patients and hospitalized patients with severe COVID-19 infections [ 23 , 37 , 46 , 49 ]. Furthermore, a study conducted by Ram-Mohan et al showed that ddPCR, compared to traditional RT-qPCR, was superior for detecting and quantifying SARS-CoV-2 RNAemia in hospitalized patients over a course of 30 days [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation